Increasing Longevity and the New Demography of Death. (23rd June 2014) - Leeson, George W.
Abstract : The world is ageing at both an individual and population levels and population ageing is truly a global phenomenon, the only notable region of exception being sub-Saharan Africa, which remains relatively young in demographic terms. At an individual level, life expectancies at birth have increased at the global level from 47 years in the mid-20th century to around 70 years today and are expected to rise to 76 years by the mid-21st century. At the population level, the proportion of the world's population aged 60 years and over has increased from 8 percent in the mid-20th century to 12 percent, and by 2050, it is expected to reach 21 percent. In Europe, ageing has continued at a slower rate, but with the emergence of increasing numbers of centenarians. This paper outlines the transition using data from England and Wales from a demography of young death in the mid-19th century to a demography of survival in the 20th century and on to the new demography of old death in the 21st century. The paper provides evidence that it is likely that ages at death will continue to increase, with more and more people reaching extreme old age. At the same time, it is likely that life expectancies at birth will continue to rise, taking life expectancy at birth in England and Wales to 100 years or more by the end of the 21st century. The new 21st century demography of death will lead to annual numbers of deaths far in excess of previous maxima.